STRESS FACTORS AFFECTING MENTAL HEALTH OF UNIVERSITY STUDENTS IN THE POST-ACADEMIC MODEL - Anzolin Lichote, Davis; da Costa Faria, Roberto; Moss Simões dos Reis, Verusca (LINKSCIENCEPLACE, 2026)
This paper aims to address the mental health of university students through a bibliographic study. In this context, it is ought to observe the possible relationships of this (mental health) to factor such as: school environment, situations of psychological and moral harassment, among others and that can lead students to changes in their mental conditions, with consequences, even physical, with possible propensity, in extreme condition, to suicide. Some observations (Nogueira, 2017) point out that the transition to higher education constitutes a change, which enables the development of conditions that lead to "stress", being that stressful factors can induce beneficial and / or harmful forms: eustress and distress, respectively; thus opening space for imbalances in the face of a strong adjustment "requirement", including behavioral ones, that normally brings impact son the student’s psychic and physical levels, generating responses in their personal (with themselves) and relational (with other human beings).In this way, the present study finds its justification before the current conjuncture, since, the subject "mental health in the universities" began to draw the attention after several occurrences, among which, the most recent ones, concern the suicide of university students in large Brazilian universities (Morais, 2018; UFRJ Macaé, 2018 e Sane, 2018). The methodology of this work will be information and data (qualitative and quantitative), as references such as: WHO (World Health Organization), articles and medical publications, research and academic work throughout the world, checking evolution and comparing, chronologically the occurrences.